Photopolymerization of highly filled dimethacrylate-based composites using Type I or Type II photoinitiators and varying co-monomer ratios. Issue 2 (February 2016) - Randolph, Luc D.; Steinhaus, Johannes; Möginger, Bernhard; Gallez, Bernard; Stansbury, Jeffrey; Palin, William M.; Leloup, Gaëtane; Leprince, Julian G.
Graphical abstract: Highlights: MAPO and CQ-based filled resin composites were mixed using four BisGMA/TegDMA ratios.. Polymerization was monitored using both FT-NIRS and DEA and post-cure properties were also determined. Initial ionic viscosity increased with BisGMA content, impacting final conversion. Specific BisGMA contents were shown to be optimal (40 mol% – MAPO or ≤20 mol% – CQ). Free and filler-bound monomer mobility and reactivity likely varied with the initiator. Abstract: Objectives: The use of a Type I photoinitiator (monoacylphosphine oxide, MAPO) was described as advantageous in a model formulation, as compared to the conventional Type II photoinitiator (Camphorquinone, CQ). The aim of the present work was to study the kinetics of polymerization of various composite mixtures (20–40–60–80 mol%) of bisphenol A glycidyl dimethacrylate/triethylene glycol dimethacrylate (BisGMA/TegDMA) containing either CQ or MAPO, based on real-time measurements and on the characterization of various post-cure characteristics. Methods: Polymerization kinetics were monitored by Fourier-transform near-infrared spectroscopy (FT-NIRS) and dielectric analysis (DEA). A range of postcure properties was also investigated. Results: FT-NIRS and DEA proved complementary to follow the fast kinetics observed with both systems. Autodecceleration occurred after ≈1 s irradiation for MAPO-composites and ≈5–10 s for CQ-composites. Conversion decreased with increasing initial viscosity for both photoinitiating systems. However despite shorter light exposure (3 s for MAPO vs 20 s for CQ-composites), MAPO-composites yielded higher conversions for all co-monomer mixtures, except at 20 mol% BisGMA, the less viscous material. MAPO systems were associated with increased amounts of trapped free radicals, improved flexural strength and modulus, and reduced free monomer release for all co-monomer ratios, except at 20 mol% BisGMA. Significance: This work confirms the major influence of the initiation system both on the conversion and network cross-linking of highly-filled composites, and further highlights the advantages of using MAPO photoinitiating systems in highly-filled dimethacrylate-based composites provided that sufficient BisGMA content (>40 mol%) and adapted light spectrum are used.